The Ice-Rich Permafrost Sequences as a Paleoenvironmental Archive for the Kara Sea Region (Western Arctic) - Streletskaya, I. D.; Pismeniuk, A. A.; Vasiliev, A. A.; Gusev, E. A.; Oblogov, G. E.; Zadorozhnaya, N. A. (Frontiers in Earth Science, 2021)
The Kara Sea coast and part of the shelf are characterized by wide presence of the ice-rich permafrost sequences containing massive tabular ground ice (MTGI) and ice wedges (IW). The investigations of distribution, morphology and isotopic composition of MTGI and IW allows paleo environmental reconstructions for Late Pleistocene and Holocene period in the Kara Sea Region. This work summarizes result of long-term research of ice-rich permafrost at eight key sites located in the Yamal, Gydan, Taimyr Peninsulas, and Sibiryakov Island. We identified several types of ground ice in the coastal sediments and summarized data on their isotopic and geochemical composition, and methane content. We summarized the available data on particle size distribution, ice chemical composition, including organic carbon content, and age of the enclosing ice sediments. The results show that Quaternary sediments of the region accumulated during MIS 5 – MIS 1 and generally consisted of two main stratigraphic parts. Ice-rich polygenetic continental sediments with syngenetic and epigenetic IW represent the upper part of geological sections (10-15 m). The IW formed in two stages: in the Late Pleistocene (MIS 3 – MIS 2) and in the Holocene cold periods. Oxygen isotope composition of IW formed during MIS 3 – MIS 2 is on average 6 ‰ lower than that of the Holocene IW. The saline clay with rare sand layers of the lower part of geological sections, formed in marine and shallow shelf anaerobic conditions. MTGI present in the lower part of the sections. The MTGI formed under epigenetic freezing of marine sediments immediately after sea regression and syngenetic freezing of marine sediments in the tidal zone and in the conditions of shallow sea.